Nilai-Nilai Toleransi dalam Fiqih Sedekah di Indonesia : Studi terhadap Pemberian Sesaji Pasca Meletusnya Gunung Semeru - Ula, Siti Khoirotul; al-Asy’ari, M. Khoirul Hadi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Recently, we were shocked by a video of a moslem youth kicking “sesaji” that placed around the mountain after the eruption of Semeru. In the video, the young man judged that the root of all natural disasters, including the eruption of Semeru, was the many “shirk” practiced which made Allah swt angry. Furthermore, this article is a fiqh research that will explain how the position of